(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Security is the first priority for everyone, everywhere. Everyone wants their home, place of business, etc. to be secure. This concept describes a security system that monitors homes and businesses. This security system is simple to setup and is functional despite its simplicity. Here, a passive infrared sensor detects individuals wherever we place it, be it at a door near our house, in an office, a factory, or any other place we need to continuously monitor for security purposes. The Raspberry Pi acts as the application’s controller in this setup. When it detects movement, a PIR sensor turns on the webcam and takes an image. The homeowner is informed of the intruder’s presence when an alarm is set off and photographs are sent to the cloud via Internet of Things technology. so that someone would know who the person who appeared at that exact moment was. A beep goes off to alert others in the vicinity in that case.